Predictors of Mortality in Scrub Typhus Infection Requiring Intensive Care Admission in Tertiary Healthcare Centre of Nepal - Adhikari, Shital; Poudel, Ramesh Sharma; Shrestha, Shakti; Lamichhane, Praves (Interdisciplinary Perspectives on Infectious Diseases, 2018)
Introduction. This study aimed to explore the predictors of mortality from scrub typhus infection in patients requiring intensive care unit (ICU) admission. Materials and Methods. A retrospective study was conducted on 120 patients with serum ELISA IgM positive for scrub typhus (optical density ≥ 0.5) admitted at the medical ICU of Chitwan Medical College Teaching Hospital between April 2016 and September 2017. Data was extracted from patient medical records and electronic database of the hospital. The outcome measurement was mortality (Yes/No) due to the infection. A multivariate binary logistic regression analysis (p<0.10) using potential variables from bivariate analysis (p<0.25) was adjusted to predict the mortality. Results. The mortality rate was 20% (24/120). Factors associated with mortality, as found using bivariate analysis, were heart rate > 100/minute (p<0.001), systolic blood pressure < 90 mmHg (p=0.025), diastolic blood pressure < 60 mmHg (p=0.032), serum creatinine > 1.4 mg/dl (p<0.001), acute kidney injury requiring dialysis (p=0.029), acute respiratory distress syndrome (p<0.001), and shock requiring vasopressor (p<0.001). Regression analysis showed age (odds ratio [OR] = 1.063; 95% CI = 1.010–1.118; p=0.019) and serum creatinine (OR = 1.063; 95% CI = 1.010–1.118; p=0.019) as significant predictors of poor outcome. Conclusion. Older age and high serum creatinine were found to be independent predictors of poor outcome in patients with scrub typhus admitted in medical ICU.